2012
DOI: 10.1097/fjc.0b013e318232b1a4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Statin Treatment Does Not Prevent Ischemia and Reperfusion-induced Endothelial Dysfunction in Humans

Abstract: Statins are known to have cholesterol-independent pleiotropic effects, such as upregulation of the enzyme ecto-5'-nucleotidase. These effects may contribute to the protective effect of statins against ischemia and reperfusion (IR). Interestingly, pleiotropic effects have been shown to differ between hydrophilic and lipophilic statins. Flow-mediated dilation (FMD) represents a largely nitric oxide-mediated, endothelium-dependent dilation and has been shown to decrease after exposure to IR in humans. FMD has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…We found a significant decrease in FMD after the IR protocol, which agrees with the observations from other groups (Kharbanda et al 2001;Loukogeorgakis et al 2006). The average decrease in FMD in our study was somewhat lower than typically observed by others (Kharbanda et al 2001;Loukogeorgakis et al 2006), but in agreement with previous observations from our laboratory (Wouters et al 2012). Differences in the magnitude of decline in FMD may relate to between study differences in the protocol to induce IR injury (i.e., longer period of ischaemia is associated with larger decline in FMD (Devan et al 2011)) or to the inclusion of different groups (Devan et al 2011).…”
Section: Discussionsupporting
confidence: 94%
“…We found a significant decrease in FMD after the IR protocol, which agrees with the observations from other groups (Kharbanda et al 2001;Loukogeorgakis et al 2006). The average decrease in FMD in our study was somewhat lower than typically observed by others (Kharbanda et al 2001;Loukogeorgakis et al 2006), but in agreement with previous observations from our laboratory (Wouters et al 2012). Differences in the magnitude of decline in FMD may relate to between study differences in the protocol to induce IR injury (i.e., longer period of ischaemia is associated with larger decline in FMD (Devan et al 2011)) or to the inclusion of different groups (Devan et al 2011).…”
Section: Discussionsupporting
confidence: 94%
“…23 However, it has been demonstrated that the administration of either lipo-or hydrophilic statins does not modulate the effect of ischaemia reperfusion injury on brachial artery FMD in healthy volunteers. 24 Of additional note, a reduction in infarct size may well be associated with short-term use and these protective effects may be lost in chronic use. 25 According to Suvorava and Kojda, repeated shortterms bouts of oxidative stress may cause the up-regulation of anti-oxidant protein expression in the vascular wall, eventually increasing its antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, most strategies that limit myocardial infarct size in animal models also conferred protection against endothelial IR-injury, although some studies could not observe protection [13], [34], [36], [37].…”
Section: Discussionmentioning
confidence: 99%